The Importance of Emotional Engagement in Improving the Performance of Amusement Rides Industry Employees in Jakarta - Aprilia Hamidah; Sarwo Edy Handoyo (Dinasti Publisher, 2023)
This research aims to explore the relationship between compensation, organizational culture, affective commitment, and employee performance in the amusement rides industry headquartered in Jakarta. This research is based on understanding more specifically how these factors are interrelated and have the potential to influence employee performance in the amusement rides industry. The research method uses a quantitative approach using Structural Equation Modeling (SEM) which is processed with the help of SmartPLS software. This research used saturated sampling or census, where 110 respondents from the employee population of the amusement rides industry at the Jakarta head office were sampled. The data collection technique was carried out by distributing questionnaires. The research results show that there is a positive relationship between fair compensation, inclusive organizational culture, and employee affective commitment. The findings also highlight that employee affective commitment acts as a mediator between compensation, organizational culture, and employee performance. The implications of this research provide a deeper understanding regarding the importance of affective commitment in strengthening the relationship between compensation, organizational culture, and employee performance in the entertainment environment. In conclusion, increasing affective commitment may be the key to improving employee performance, which is necessary for companies to achieve business goals and provide the best experience to customers.